Electrocatalytic Reduction of CO2 on Cu and Au/W Electrode Surfaces: Empirical (DEMS) Confirmation of Computational (DFT) Predictions. (4th January 2017) - Javier, Alnald; Baricuatro, Jack Hess; Kim, Youn-Geun; Soriaga, Manuel P
Abstract : This work describes the employment of differential electrochemical mass spectrometry (DEMS) as a supplementary experimental approach to theory in the study of the reaction mechanism of the Cu-catalyzed electrochemical reduction of CO2 by investigating the reduction of reactants and (postulated) intermediates. The empirical inferences: (i) CO is one of the first products of CO2 reduction, as well as the first intermediate in the formation of more reduced products. (ii) Formaldehyde is not a precursor for C=C bond formation but is an intermediate for the production of methane and ethanol. (iii) Both methane and ethanol can be generated from CO2 through the protonation of CO and through the HCHO intermediate. (iv) The generation of CH4 and CH3 CH2 OH from CO and CO2 has a much higher activation barrier than from HCHO; not unexpected since the formaldehyde intermediate is formed after the (computationally determined) rate-limiting CO-protonation step. In this work, DEMS was also used to test the theoretical prediction suggesting the viability of a bimetallic near-surface alloy (NSA) consisting of Au and W as a CO2 -reduction electrocatalyst selective towards the formation of methanol as a product, as opposed to methane, ethylene or ethanol. At an overlayer NSA that consisted of n monolayers (ML) of Au on a polycrystalline W electrode, W(pc)- n [(1×1)-Au], no methane, methanol, ethylene or ethanol was detected when the coverage of Au was at submonolayer ( n = 0.5) or multilayer ( n ≥ 2) coverages. However, when the NSA contained only 1 ML of Au, methanol was generated exclusively.